RED REFLEX-SIMPLE YET EFFECTIVE SCREENING TOOL IN THE NEWBORN: A CROSS-SECTIONAL STUDY. - Dash, Rutayani; Mohapatra, Satyaranjan; Panda, Jitendra; Bhoi, Radhakanta (Student’s Journal of Health Research Africa, 2024)
Background The red reflex is practically easy to execute, non-intrusive, needs a minimum instrument, and identifies various ocular disorders. Red reflex examination in the infant is advised for the early diagnosis and management of ocular abnormalities. The prime goal of this research is to examine the outcome of the red reflex test in infants. Materials and Methods A retrospective cross-sectional research was carried out in which 100 newborn babies were included for one year. All the detailed history of the patients was recorded. The test was carried out in a dark room with the new baby on the lap of the parent. Notably, dilation was performed selectively: only infants with a history of ocular abnormalities underwent pupil dilation using 0.8% tropicamide with 2.5% phenylephrine before the examination. Results 56 newborn babies were male and 44 newborn babies were female. 68 patients had normal vaginal delivery and 32 patients had C-sections. 24 children had red reflex, 14 children had Orange red reflex, 52 children had orange reflex, 8 children had grayish white reflex and 2 children had black shadow reflex. Conclusion In the present research it was concluded that the red reflex test has great precision and, therefore helps in diagnosing ocular disorders in newborn babies. It is observed that the red reflex is the less time-consuming and economical procedure for detecting ocular defects. The red reflex test is an easy-to-perform and secure method for the examination of the eyes. Recommendation Newborns should receive a red reflex test before leaving the medical center. Normal results indicate consistent color, intensity, and transparency in both eyes. Abnormal results warrant referral to an ophthalmologist for early diagnosis and prevention of visual disabilities.